(untitled) (Research, Society and Development, 2023)
Ceramic blocks are materials widely used in Brazilian civil construction. However, according to data from the Ministry of Regional Development (2021), only 44.3% of the blocks sold are in accordance with the Brazilian Association of Technical Standards (ABNT). This study analyzed the quality of ceramic sealing blocks marketed in the city of Itabira/MG from the characterization of the blocks according to the Brazilian Technical Standard 15270 (2017) with the objective of evaluating rather the products sold reach the parameters required by standard. Based on the analysis of the proportion of units of six brands marketed in the city, the result was rejection in at least two of the tests, that is, none of the brands would be fit for use in accordance with the established quality standards. In addition, an estimate of the increase in the volume of coating material was performed in case there was a variation in the settlement face of the blocks, for this determination, the result was also expressive, with an average increase of 20% in the material volume cost, which can have a great impact on the final budget of a project. These results confirm the problem faced by the sector with regard to the precariousness of quality control of manufactured products, in addition to reflecting the need to increase inspection of final products, investments in technical training of producers and the search for quality certification by customers.